Have you seen my duckling? - Tafuri, Nancy (New York : Greenwillow Books, 1984)
A mother duck leads her brood around the pond as she searches for one missing duckling.
Wilson's Children, October 2006
Elem. School Library Collection, June 2000
School Library Journal, February 2006
Booklist, September 2002
Horn Book, May 2004
1.5
Keywords: Lost children -- Fiction; Ducks -- Fiction; Ponds -- Fiction; Ducks -- Fiction; Ponds -- Fiction; Missing children -- Fiction